Land, Nation and Culture, 1740–1840
XII, 246 p.
Keywords: Over the last twenty years, critics and historians of the late Eighteenth-century have developed a multidisciplinary approach to the history of culture. This dialogue between literary critics and theorists, art historians and social historians is remapping the relations between culture and society, politics and aesthetics, law and representation. These essays by twelve internationally known scholars return 'Taste' to a central position in the discussion of nation, culture and aesthetics in the period.